METHODOLOGY FOR USING ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN GENERAL SECONDARY SCHOOLS - Xolmo‘minova Madina Islombek qizi; Ergashev Muzaffar Abdukasimovich (Uzbekistan Open Conference, 2026)
This article examines the pedagogical and methodological aspects of using artificial intelligence (AI) technologies in general secondary schools. It analyzes the integration of AI-based educational tools into the learning process and their role in developing students’ knowledge, skills, and competencies. The paper also identifies challenges arising from the use of AI technologies and proposes solutions to address them.
Keywords: artificial intelligence; digital education; educational technologies; adaptive learning; methodology